Work of family health strategy nurses in oncology care - Geize Rocha Macedo de Souza; Luiza Helena de Oliveira Cazola; Sandra Maria do Valle Leone de Oliveira (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To identify the qualification of and to know the work of Family Health Strategy nurses in oncology care. Methods: A cross-sectional, descriptive study, using a quantitative approach, was conducted with 77 nurses working in the Family Health Strategy units of Campo Grande, state of Mato Grosso do Sul. Primary data were collected in structured interviews, using a form with closed-ended questions. Results: Professional training in oncology care is less frequent, reflecting a high lack of knowledge regarding the National Policy on Oncology Care. It was evidenced that 95% of the professionals assisted oncology patients, with home visits and nursing appointments being the most prevalent methods. Regarding the National Policy on Oncology Care, 96% of the nurses declared that they did not know about it. Conclusion: There was evidence of weakness in the care provided by the nurses to oncology patients and the need for investment in continuing education for professional nurses regarding oncology care.